Stepping backwards with disability humor? The case of NY Gov. David Paterson’s representation on ‘Saturday Night Live’ - Haller, Beth; Becker, Amy Bree (Disability Studies Quarterly, 2014)
In the modern era, discerning TV viewers know the shows that trade in cheap laughs by making fun of people with disabilities are not tapping into much creativity. So it was a surprise in 2008 when the highly regarded comedy show Saturday Night Live (SNL) stooped to that level by ridiculing the blind governor of New York, David Paterson, in a series of sketches lasting two years. This article analyzes the way humor narratives about a high-profile blind politician on television, like those depicted in the SNL skits, may have influenced larger cultural themes about blindness. Because the East Coast news media reported on the SNL skits every time an episode aired, this project undertook a textual analysis of all aspects of the controversy including the content of the SNL skits, the repeated responses from Gov. Paterson and the blindness community, and the news media framing of the SNL-Paterson skit story. This analysis examines the intertextuality of the event, revealing that the blindness community had a very different reading of the SNL skits, due to concerns about continuing media narratives that devalue and stereotype them. Keywords: blindness, disability humor, TV comedy shows, skit comedy, politicians